'Living with the floods': the influence of relational and cognitive capital on disaster risk management capacities in Ratnapura, Sri Lanka. Issue 1 (2nd January 2019) - Ahangama, Nadeera; Prasanna, Raj; Blake, Denise
ABSTRACT: Developing multi-stakeholder networks to transfer response and recovery related knowledge between government agencies and flood-prone communities has become an important component of contemporary disaster risk management policy development in South-Asia. Despite the growing desire of governments to engage communities in flood resilience, knowledge of the effectiveness of such measures is still scarce. This research discusses the implications of relational and cognitive social capital on knowledge transfer practices for two disaster risk management stakeholder groups in the Ratnapura district of Sri Lanka. Findings indicate that community stakeholders use social networks within their neighbourhood as a primary survival strategy for 'living with the floods'; however, district-level committees find it difficult to facilitate long-term approaches, allocating responsibilities for knowledge transfer and risk reduction. It is concluded that the government efforts to achieve long-term flood resilience goals stand more chance of success if multi-stakeholder networks are capable of bridging this perceptual gap.